The COSPAR planetary protection policy for missions to Icy Worlds: A review of history, current scientific knowledge, and future directions - P.T. Doran; A. Hayes; O. Grasset; A. Coustenis; O. Prieto-Ballesteros; N. Hedman; O. Al Shehhi; E. Ammannito; M. Fujimoto; F. Groen; J.E. Moores; C. Mustin; et al. (Life Sciences in Space Research, 2024)

Consensus Paper. Cerebellar Reserve: From Cerebellar Physiology to Cerebellar Disorders - H. Mitoma; A. Buffo; F. Gelfo; X. Guell; E. Fucà; S. Kakei; J. Lee; M. Manto; L. Petrosini; A.G. Shaikh; J.D. Schmahmann (The Cerebellum, 2020)
Cerebellar reserve refers to the capacity of the cerebellum to compensate for tissue damage or loss of function resulting from many different etiologies. When the inciting event produces acute focal damage (e.g., stroke, trauma), impaired cerebellar function may be compensated for by other cerebellar areas or by extracerebellar structures (i.e., structural cerebellar reserve). In contrast, when pathological changes compromise cerebellar neuronal integrity gradually leading to cell death (e.g., metabolic and immune-mediated cerebellar ataxias, neurodegenerative ataxias), it is possible that the affected area itself can compensate for the slowly evolving cerebellar lesion (i.e., functional cerebellar reserve). Here, we examine cerebellar reserve from the perspective of the three cornerstones of clinical ataxiology: control of ocular movements, coordination of voluntary axial and appendicular movements, and cognitive functions. Current evidence indicates that cerebellar reserve is potentiated by environmental enrichment through the mechanisms of autophagy and synaptogenesis, suggesting that cerebellar reserve is not rigid or fixed, but exhibits plasticity potentiated by experience. These conclusions have therapeutic implications. During the period when cerebellar reserve is preserved, treatments should be directed at stopping disease progression and/or limiting the pathological process. Simultaneously, cerebellar reserve may be potentiated using multiple approaches. Potentiation of cerebellar reserve may lead to compensation and restoration of function in the setting of cerebellar diseases, and also in disorders primarily of the cerebral hemispheres by enhancing cerebellar mechanisms of action. It therefore appears that cerebellar reserve, and the underlying plasticity of cerebellar microcircuitry that enables it, may be of critical neurobiological importance to a wide range of neurological/neuropsychiatric conditions.

Consensus Paper: Cerebellar Development - Ketty Leto; Marife Arancillo; Esther B. E. Becker; Annalisa Buffo; Chin Chiang; Baojin Ding; William B. Dobyns; Isabelle Dusart; Parthiv Haldipur; Mary E. Hatten; Mikio Hoshino; Alexandra L. Joyner; et al. (The Cerebellum, 2016)

Restrained shrinkage of massive reinforced concrete structures: results of the project CEOS.fr - L. Buffo-Lacarrière; S. Baron; F. Barré; D. Chauvel; A. Darquennes; J.-P. Dubois; J. Gayete; F. Grondin; B. Kolani; H. Lançon; A. Loukili; G. Moreau; et al. (European Journal of Environmental and Civil Engineering, 2016)